2016
DOI: 10.1542/peds.2015-3275
|View full text |Cite
|
Sign up to set email alerts
|

Swaddling and the Risk of Sudden Infant Death Syndrome: A Meta-analysis

Abstract: CONTEXT: Swaddling is a traditional practice of wrapping infants to promote calming and sleep. Although the benefits and risks of swaddling in general have been studied, the practice in relation to sudden infant death syndrome remains unclear. OBJECTIVE:The goal of this study was to conduct an individual-level meta-analysis of sudden infant death syndrome risk for infants swaddled for sleep.DATA SOURCES: Additional data on sleeping position and age were provided by authors of included studies. STUDY SELECTION:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…However, these terms are not synonymous. As several authors have highlighted [12,26,56] studies which use different criteria to define the same term create a confusing array of information that cannot easily be compared. This leads to further confusion among healthcare professionals and parents when interpreting and understanding safe sleep recommendations and the supporting evidence of such guidelines for infant sleep location.…”
Section: Discussionmentioning
confidence: 99%
“…However, these terms are not synonymous. As several authors have highlighted [12,26,56] studies which use different criteria to define the same term create a confusing array of information that cannot easily be compared. This leads to further confusion among healthcare professionals and parents when interpreting and understanding safe sleep recommendations and the supporting evidence of such guidelines for infant sleep location.…”
Section: Discussionmentioning
confidence: 99%
“…Swaddled infants should always be placed supine to sleep and swaddling should be stopped as soon as infants show any signs of being able to roll. Evidence for this comes from a recent meta‐analysis which identified that swaddling risk varied according to position placed for sleep; the risk was highest for prone sleeping (OR = 12.99 (95% confidence interval (CI) = 4.14–40.77)), followed by side sleeping (OR = 3.16 (95% CI = 2.08–4.81)) and supine sleeping (OR = 1.93 (95% CI = 1.27–2.93)) . There was evidence to suggest swaddling risk increased with infant age and was associated with a twofold risk for infants aged >6 months …”
Section: Evidence For Safe Sleeping Recommendationsmentioning
confidence: 99%
“…The issue of swaddling's effect on SIDS, however, is far from settled and actually quite controversial. While some studies show that swaddling may protect against it (Richardson et al 2009) others show that it may increase it (Pease et al 2016). The verdict is, hence, still out.…”
Section: Eye Contact and Threatmentioning
confidence: 99%